Maritima Expo the Cebu City waterfront heritage district museum revitalization of the Cebu City waterfront heritage District :a case-study on the adaptive reuse of Compania Maritima - Soringa, Rojeno A.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The Cebu City Waterfront Heritage District was once the urban center of Cebu City until urban functions transferred to the developments in its periphery; thus, leaving the district in a state of urban decay manifested by obsolete land use and physical configuration, limited economic functions and low economic productivity, worsening traffic conditions, insusceptibility to investments, derelict buildings, and undervalued built heritage. In Line with the Urban revitalization program for the district, this design-based research engages in adaptive reuse, which is a strategy in the practice of conservation which promotes the conservation of cultural heritage and the enhancement of the built environment. Fernandez Building, more popularly known as Compania Maritima, a landmark heritage source at the southern edge of the Cebu City Waterfront Heritage District, is used as the building chosen for adaptive reuse. This issue-based research aims to generate an adaptive reuse model in the context of the Cebu City Waterfront Heritage District, to document the current sate of Compania Maritima, and ultimately, to create an architectural design which highlights the character of the urban fabric. The adaptive reuse process undertaken by this design-based research follows the outline proposed by Misirhsoy & Gunce (2016). And to further illustrate the current state of Compania Maritima in terms of its useful life, the adaptive reuse potential model proposed by Langston (2008) is used. After performing the decision-making process by Misirhsoy & Gunce (2016), this design-based research proceeds to the architectural design translation and adaptive reuse of Compania Maritima as a part of the Cebu City Waterfront Heritage District Museum.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Museum -- Architectural design